Dystrophinopathy Diagnosis Made Easy: Skin Biopsy, an Emerging Novel Tool. (April 2014) - Chakrabarty, Biswaroop; Sharma, M. C.; Gulati, Sheffali; Kabra, Madhulika; Pandey, R. M.; Sarkar, Chitra
Dystrophinopathies are diagnosed by genetic studies and muscle biopsy. Most centers have multiplex polymerase chain reaction facilities diagnosing 65% to 70% of dystrophinopathy cases. Muscle biopsy is a time-consuming, invasive procedure whereas skin biopsy is a simple procedure done under local anesthesia. The current study evaluated the diagnostic accuracy of skin biopsy in dystrophinopathy. Overall, 119 confirmed cases of muscular dystrophy (111 males and 8 females) were included in the final analysis, of which 100 (all males) were dystrophinopathy. Skin biopsy diagnosed dystrophinopathy in suspected muscular dystrophy patients with a sensitivity of 98% (92.3%-99.7%), specificity of 99% (93.7%-99.9%), positive predictive value of 94.7% (71.9%-99.7%), and negative predictive value of 90% (66.9%-98.2%). Skin biopsy can be used for screening dystrophinopathy in muscular dystrophy patients (high sensitivity and positive predictive value). It being a simple and minimally invasive procedure, histopathologic and molecular markers of disease progression and response to novel treatment options can be assessed serially.